China's belt and road initiative : potential transformation of Central Asia and the South Caucasus - Kohli, Harinder S., 1945- (Sage Publications India, 2019)
China's Belt and Road Initiative (BRI) is a potential gamechanger for the Central Asia and South Caucasus (CASC) region. CASC countries naturally view this massive development program as a unique opportunity to accelerate their economic development through increased foreign investment, upgraded physical infrastructure, and tighter economic relationships with their neighbors. Yet embracing the BRI is not without risks. Some BRI investments may prove to be fiscally unsustainable, economically and financially unviable, and socially and environmentally harmful. Inadequate cross-border coordination and infrastructure maintenance could render some BRI investments wasteful or redundant. If not proactively addressed, these risks have the potential to leave countries worse off for having participated in the BRI. Policymakers in the CASC region and their development partners, thus, face a daunting question: how to realize the promise of the BRI for their countries while avoiding the pitfalls that lie along the way? This book attempts to answer this question by leveraging the unique insights of development experts in the CASC region. Drawing on the most comprehensive review of BRI investment data conducted to date, this book presents a dynamic policy agenda that is relevant to any country in which China is building the Belt and Road.